Mengatasi Krisis Moneter Melalui Penguatan Ekonomi Rakyat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT The Indonesian economy in the year 2000 grew 4,77 percent after only 0,23 percent growth in the previous year, due to the strong growth of physical investment and export. Any economy that is growing 5 percent a year with inflation below 10 percent is certainly not in crisis condition. However, the "complete loss of investor confidence" indeed has not restored because of political uncertainty and insecurity. The paper argues that the dualistic nature of the Indonesian economy and the important role of the ekonomi rakyat (people's economy) is instrumental in explaining the phenomena. Another phenomenon that must be considered is the wide regional variation, meaning that the economic and monetary crisis affecting Java's economy negatively>, may become "bonanza" to other regions producing export commodities. The regional variation especially in the Human Development Index also means that indeed backward regions should be able to learn from other regions having better quality of human resources. Finally lessons can be learned from countries like India and China that has not liberalized their economy too far. The 1997 crisis has taught a hard lesson to Indonesia.